Pengaruh Pembayaran QR Code terhadap Kepuasan Pelanggan pada Mahasiswa - Veronika Elsanti (International Journal Administration, Business & Organization, 2022)
The purpose of this study is aims to reveal the influence of the QR Code payment system on customer satisfaction among students. The respondents of this research are students who have or have used digital payments with the help of QR Codes anywhere and anytime. This research was analyzed with the help of quantitative descriptive methods using validity and reliability tests, as well as simple linear regression tests. The data obtained in this research is the result of distributing online questionnaires via Google Form to 102 college students with the help of social media. The research results show that the QR Code payment system has an effect on customer satisfaction among students with a value of 78.2%.